Worldwide Research on Low Cost Technologies through Bibliometric Analysis - Salmerón-Manzano, Esther; Manzano-Agugliaro, Francisco (Inventions (Basel), 2020)
It is essential to address research into low-cost technologies, as those employed on a wide scale demand a great amount of resources. The main goal of this work was to analyze the research on low cost technologies worldwide by studying the scientific output recorded in the Scopus database. This analysis makes it possible to determine the evolution of research into low cost technologies. In particular, we analyzed the distribution of this research by the different scientific categories, the categories’ evolution over time, the types of publications, the geographical distribution throughout different countries, the main institutions in each scientific category, and the areas of research identified through the main keywords indexed in the publications. A remarkable finding of this work has been that the universities that are most active in low-cost technologies are those in the most technologically advanced countries. There is only one exception to the above statement and it is in the field of medicine, where the most technologically developed countries are not always the most interested in this field. Given the trends observed in recent years, there is a need for a major change and for low-cost technologies to become an area of interest in countries with emerging economies.